Soil microbial community structure and activity in monospecific and mixed forest stands, under Mediterranean humid conditions - Lucas-Borja, M. E.; Candel, D.; Jindo, K.; Moreno, J. L.; Andrés, M.; Bastida, F. (Plant and Soil, 2011)
Aims We investigated the link between tree community composition and soil microbial community biomass and structure in central-eastern Spain. Methods The effects of the forest stand composition on the soil organic matter dynamics and on the structure and activity of the soil microbial community have been determined using phospholipid fatty acid profiles and soil enzymatic activities. Results The soil and litter N and C contents were higher in Pinus nigra Arn. ssp. salzmannii and Quercus ilex mixed forest stands (SBHO) and in long-term unmanaged Pinus nigra Arn. ssp. salzmannii forest stands (SBPC) than in pure Pinus nigra Arn. ssp. salzmannii forest stands (SBPA) and Pinus nigra Arn. ssp. salzmannii and Juniperus thurifera mixed forest stands (SBSJ). The bacterial biomass was significantly higher in SBSJ and SBPA than in SBPC and SBHO. The results show an uncoupling of the soil microbial biomass and its activity. pH is related to microbial biomass and its community structure under a Mediterranean humid climate. Conclusions The tree species seem to affect the biomass of the soil microbial community and its structure. The pH, but not the C/N ratio, is a factor influencing the microbial dynamics, biomass, and community structure.
Keywords: Microbial biomass; phospholipid fatty acids; Soil; Soil enzymes; Soil organic matter; spanish black pine